Impact of Chronic Kidney Disease Severity on the Risk of Prurigo Nodularis: A Population-Based Cohort Study - Hei Sung Kim; Hyun Jung Kim; Hyeong Sik Ahn (Medical Journals Sweden, 2022)
While dialysis is linked with prurigo nodularis, little is known about the impact of non-dialysis chronic kidney disease on prurigo nodularis. The influence of chronic kidney disease on development of prurigo nodularis was measured using the Korean National Health Insurance and National Health Screening Program data, identifying 17,295,576 individuals without prior prurigo nodularis. Chronic kidney disease severity was determined by the estimated glomerular filtration rate (in ml/min/1.73 m2) calculated from serum creatinine, and proteinuria detected with urine dipstick. Prurigo nodularis incidence during follow-up was determined. Over a median follow-up period of 9.72 years, 58,599 individuals developed prurigo nodularis, with an incidence rate of 3.59 per 10,000 person-years. Among different variables, estimated glomerular filtration rate was the strongest risk factor for prurigo nodularis. Compared with estimated glomerular filtration rate ≥ 90, estimat-ed glomerular filtration rate 15-29 (hazard ratio 1.31, 95% confidence interval 1.05-1.62) and end-stage renal disease (hazard ratio 1.46, 95% confidence interval 1.25-1.69) were associated with higher risks. The presence of proteinuria independently increased the risk of prurigo nodularis, increased risks associated with estimated glomerular filtration rate 15-29 and end-stage renal disease, and caused risk associated with estimated glomerular filtration rate 30-59 to become significant. With differential impact of chronic kidney disease severity on the risk of prurigo nodularis, preservation of renal function would potentially translate into lower risk of prurigo nodularis.